Presupposition in the Character of Judy: A Pragmatic Analysis of the Zootopia Movie Script - Asro, Siti Aslihatun Ni'mah; Andriyani, Santi (LP2M IAIN Sultan Amai Gorontalo, 2025)
Background: A well-grounded and accurate assumption helps in selecting appropriate lexical variations before expressing a statement in communication. Movies serve as an effective medium for this purpose, as they reflect real-life situations. In pragmatics, presuppositions allow listeners to recognize implied meanings and better understand communicative intentions. Aims: This study examines the use of presuppositions in the Zootopia movie script by applying George Yule’s (1996) theory of presupposition. It aims to identify the types of presuppositions expressed in the dialogue, analyze the educational character values demonstrated by the main character, and interpret the meanings conveyed through presuppositions in the movie script. Methods: The study employed a qualitative content analysis design. The data were collected from the dialogues of the main character in the Zootopia movie script. Results: A total of 106 presuppositional instances were identified. Existential and factual presuppositions were the most frequently occurring types. Additionally, five educational character values were found: (1) peacemaker, (2) curiosity, (3) discipline, (4) responsibility, and (5) hard work. Implication: The interpretation of presuppositions allows audiences to gain deeper insights into the underlying meanings of the dialogue. Through movie scripts, viewers can not only engage with the storyline and character development but also grasp the film’s core messages and objectives. Future research should extend beyond presuppositions to explore a broader range of linguistic phenomena.